"Learning Outcome" as a Theological Concept: Skills, Competences, and Personal Development in Theological Education. Issue 2 (3rd November 2014) - Marsh, Clive
Abstract : This article examines the purpose and effectiveness of "learning outcomes" within theological education in the face of charges that they primarily serve the needs of managers and bureaucrats rather than educators. Drawing on theories about outcomes and recent evidence-based reflections on their usefulness for students, the paper argues that they are indeed pedagogically beneficial. They can be of particular use in theological education when viewed within the overall context within which such education occurs i.e. the development of the whole person. It is, however, essential that the limitations of what learning outcomes can achieve is also recognized, acknowledging that much more can, and is likely to, be learned in programmes than outcomes at session, module or course level can possibly encapsulate.